DASAR-DASAR NORMATIF DAN PENALARAN FILOSOFIS TENTANG HAKEKAT KEIMANAN - -, Suryanto (UNIVERSUM, 2016)
Belief is a main thing as a basis of Muslim’s life. Without having belief, how good of Muslim’s attitude will not mean anything. As also in the opposite, a belief without manifestation in good behavior will decrease the belief meaning. In belief discussion, it can be categorized into two types, namely traditional thinking method and rational thinking method. The first paradigm is built by Ash’ariyah; meanwhile, the second is built by Mu’tazilah. In classic era, the debatable between the both approaches in solving religious problems is really sharp. The openness issues in globalization, knowledge and technology that cannot be stopped anymore, pushes people to find new alternative by using a more nuance approach. Socio-philosophy-Qur’anis approach becomes new normative basis in this article to discuss the matter of belief so that it can be found the belief model that integrates the belief and the action based on philosophy principles.Keywords; Normative basis, Philosophy reasoning, Belief.